Evaluation of the cytotoxic effects of Cyperus longus extract, fractions and its essential oil on the PC3 and MCF7 cancer cell lines - MEMARIANI, TOKTAM (Oncol Lett, 2016)
Cyperus longus is one of the Iranian endemic species. However, to date, and to the best of our knowledge, there are no availale academic reports on the cytotoxicity of this plant. Thus, this study was carried out to examine the in vitro anti-proliferative and anti-apoptotic effects of Cyperus longus extract, fractions and essential oil (EO) on MCF7 and PC3 cell lines. The chemical constituents of EO were identified using gas chromatography (GC)-mass spectrometry (MS) analysis. The cells were cultured in RPMI-1640 medium and incubated with various concentrations of the plant extract and fractions. Cell viability was quantified by MTT assay following 24, 48 and 72 h of exposure to (12.5–200 µg/ml) of the methanol extract, the dichloromethane (CH(2)Cl(2)), ethyl acetate (EtOAc) and water fractions, as well as the EO of the plant. The percentage of apoptotic cells was determined using propidium iodide staining of DNA fragments by flow cytometry (sub-G1 peak). The most effective fraction in the MCF7 cell line was the CH(2)Cl(2) fraction (IC(50) after 48 h, 25.34±2.01). The EtOAc fraction (IC(50) after 48 h, 35.2±2.69) and the methanol extract (IC(50) after 48 h, 64.64±1.64) were also found to be effective. The IC(50) values obtained for the PC3 cell line were 37.97±3.87, 51.57±3.87 and 70.33±2.36 for the CH(2)Cl(2) fraction, the EtOAc fraction and the methanol extract, respectively. Based on these data and due to the partial polarity of the most effective fraction (the CH(2)Cl(2) fraction), we also examined the cytotoxicity of the plant EO. The IC(50) values after 48 h were 22.25±4.25 and 12.55±3.65 in the PC3 and MCF7 cell lines, respectively. DNA fragmentation assay also confirmed these data. Performing GC-MS analysis for the plant EO revealed that β-himachalene (10.81%), α-caryophyllene oxide (7.6%), irisone (4.78%), β-caryophyllene oxide (4.36%), humulene oxide (12%), viridiflorol (4.73%), aristolone (6.39%) and longiverbenone (6.04%) were the main constituents. Our results demonstrated that two of the constituents of Cyperus longus, viridiflorol and longiverbenone, should be investigated further as possible promising chemotherapeutic agents in cancer treatment.